Central Bank Financial Strength and Policy Performance : An Econometric Evaluation - Stella, Peter (IMF Working Papers; Working Paper ;, 2008)
The financial health of central banks and its relation to policy outcomes has recently been recognized as an important policy issue. While case study evidence clearly indicates that weak central bank finances can hamper effective policy implementation, the question of whether central bank financial strength influences policy performance remains controversial. This is due, in part, to a lack of econometric evidence. The paper presents a first step toward filling this gap, by providing a quantitative evaluation of the relationship between measures of central bank financial strength and policy performance, in particular inflation. The paper's major finding is that there indeed is a negative relationship between central bank financial strength and inflation outcomes. This relationship appears to be robust to the choice of alternative country samples, control variables, estimation strategies, and conceptualizations of central bank financial strength.